Pengaruh Organizational Justice dan Employee Engagement terhadap Organizational Citizenship Behavior Karyawan - Artajaya, Made; Pratama, Akbar (Prasetiya Mulya Publishing, 2020)
The management of InterContinental Bali Resort applies two policies, which are organizational justice and employee engagement that expected to be able to improve organizational citizenship behavior in ought to increase employee performance, especially those dealing directly with guests, one of it is F&B Service Department. This study aims to analyze the influence of organizational justice and employee engagement on organizational citizenship behavior partial and simultaneous F&B Service Department employees at InterContinental Bali Resort. Determination of samples using saturated sample techniques totaling 78 respondents. Data collection techniques used were questionnaires. This research was conducted using multiple linear regression analysis techniques, t-test, F-test and determination coefficient analysis (R2) with the help of SPSS version 22. The results of the analysis showed that (1) organizational justice (X1) had a positive and significant effect partial to organizational citizenship behavior (Y), (2) employee engagement (X2) has a positive and significant effect partially on organizational citizenship behavior (Y), and (3) organizational justice (X1) and employee engagement (X2) positive and significant influence simultaneously on organizational citizenship behavior (Y). The results of the coefficient of determination analysis (R2) show that organizational justice and employee engagement has an effect of 59.7% on organizational citizenship behavior, while the remaining 40.3% is influenced by other variables not discussed in this study.